Development of Career Brochures as a Career Information Service Medium for Students - Sal Sabilah Jahra; Ali Daud Hasibuan (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aimed to develop a career brochure based on Holland’s Theory (RIASEC) as a career information service medium for students and to examine its feasibility and practicality. The study employed a Research and Development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The research subjects were eleventh-grade students of MAS Nurul Fadhilah Medan selected through purposive sampling. The research instruments included a needs assessment questionnaire, material and media expert validation sheets, and student and teacher response questionnaires. The validation results indicated that the career brochure obtained a score of 90% from the material expert and 91% from the media expert, both categorized as very good. The practicality test results showed percentages of 97.25% based on students’ responses and 83.3% based on the guidance and counseling teacher’s response, both of which were categorized as highly practical. The findings revealed that the developed career brochure is feasible and practical for use as a career information service medium. Furthermore, it assists students in understanding their personality types, identifying suitable career options, and planning their future careers more effectively and systematically.